Effect of Different Cryopreservation Regimens on Bone Marrow Hemopoietic Stem Cell Integrity in Animals With Autoimmune Diseases Part 2. In vivo Estimation of Functional Status of Cryopreserved Bone Marrow Hemopoietic Progenitors - Goltsev, A. N.; Dubrava, T. G.; Kozlova, A. Yu.; Ostankov, M. V.; Gurina, T. M.; Kurov, A. M. (Problems of Cryobiology and Cryomedicine, 2007)
Functional characteristics of bone marrow hemopoietic stem cells of healthy animals and with autoimmune diseases before and after cryopreservation with different regimens have been comparatively determined in vivo. The principle differences between an initial functional status of hemopoietic precursors of healthy donors and with autoimmune diseases, as well as its changes under similar cryopreservation conditions have been demonstrated. The â€œoptimumâ€ of CFUs colony-forming activity of healthy animals and those with adjuvant arthritis was noted as realised under bone marrow cryopreservation with different regimens.